Ultrasound-guided acupotomy for cervical spondylosis: a systematic review and meta-analysis based on GRADE quality assessment - Lijian, Zhang; Zhen, Zhang; Yuan, Yuan; Nachuan, Zhang (Frontiers in Pain Research, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of ultrasound-guided acupotomy (UgA) in treating Cervical spondylosis (CS), particularly in pain relief, improvement in cervical range of motion (CROM), and overall clinical efficacy, through a systematic review and meta-analysis based on GRADE quality assessment.MethodsFollowing PRISMA guidelines, we searched databases including PubMed, Embase, Cochrane Library, Web of Science, and CNKI, Wanfang, Weipu, and Sinomed, identifying 33 randomized controlled trials (RCTs). Inclusion criteria were: patients aged 18–70 with a diagnosis of CS, intervention with UgA, and control groups receiving placebo, physical therapy, or other conventional treatments. Primary outcomes included clinical effective rate and Visual Analog Scale (VAS) for pain, while secondary outcomes encompassed Neck Disability Index (NDI), CROM, and mean flow velocity of vertebral and basilar arteries (MFV-VA/BA). Study quality was assessed using the Cochrane Risk of Bias 2.0 tool, and meta-analysis was conducted using Stata 15.0. The GRADE approach was used to evaluate evidence quality.ResultsMeta-analysis revealed that UgA significantly improved the clinical effective rate compared to control treatments (RR = 1.17, 95% CI: 1.13–1.21), with low heterogeneity (I2 = 12%). UgA also demonstrated significant pain reduction (WMD = −0.96, 95% CI: −1.25 to −0.67), albeit with high heterogeneity (I2 = 91.6%). For secondary outcomes such as NDI, CROM, and MFV-VA/BA, UgA showed moderate improvements, but with considerable heterogeneity. GRADE assessment indicated high-quality evidence for the clinical effective rate, while evidence for VAS, NDI, and CROM was rated as low or very low due to heterogeneity and publication bias.ConclusionUgA shows superior efficacy for pain and disability in cervical spondylosis compared to non-UgA and other acupuncture related therapies. However, heterogeneity and potential publication bias exist. It requires skilled practitioners and real-time ultrasound guidance for treatment. Future multinational randomized trials with standardized protocols are needed.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/PROSPERO, PROSPERO CRD42025649835.